2014
DOI: 10.1162/jocn_a_00494
|View full text |Cite
|
Sign up to set email alerts
|

Direct Control of Visual Perception with Phase-specific Modulation of Posterior Parietal Cortex

Abstract: We examined the causal relationship between the phase of alpha oscillations (9-12 Hz) and conscious visual perception using rhythmic TMS (rTMS) while simultaneously recording EEG activity. rTMS of posterior parietal cortex at an alpha frequency (10 Hz), but not occipital or sham rTMS, both entrained the phase of subsequent alpha oscillatory activity and produced a phase-dependent change on subsequent visual perception, with lower discrimination accuracy for targets presented at one phase of the alpha oscillato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
75
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(82 citation statements)
references
References 38 publications
3
75
0
Order By: Relevance
“…Yet, one needs to distinguish experiments examining the role of entrained oscillations from experiments investigating the role of ongoing endogenous oscillations. In several studies, relevant events follow a specific rhythm to which participants can entrain in a bottom-up fashion (Jaegle & Ro, 2014;Spaak et al, 2014;Cravo et al, 2013;De Graaf et al, 2013;Rohenkohl, Cravo, Wyart, & Nobre, 2012;Besle et al, 2011;Mathewson, Prudhomme, et al, 2011;Lakatos et al, 2008Lakatos et al, , 2009. In these experiments, the phase of the entrained oscillations (as delta, theta, and alpha) is generally found to modulate perception.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, one needs to distinguish experiments examining the role of entrained oscillations from experiments investigating the role of ongoing endogenous oscillations. In several studies, relevant events follow a specific rhythm to which participants can entrain in a bottom-up fashion (Jaegle & Ro, 2014;Spaak et al, 2014;Cravo et al, 2013;De Graaf et al, 2013;Rohenkohl, Cravo, Wyart, & Nobre, 2012;Besle et al, 2011;Mathewson, Prudhomme, et al, 2011;Lakatos et al, 2008Lakatos et al, , 2009. In these experiments, the phase of the entrained oscillations (as delta, theta, and alpha) is generally found to modulate perception.…”
Section: Discussionmentioning
confidence: 99%
“…Growing evidence from electrophysiological recordings suggests that the discreteness of perception might be associated to oscillatory processes in the brain. Several studies have shown that the phase of oscillations in the alpha band (8-12 Hz) is related to several perceptual processes (Jaegle & Ro, 2014;Spaak, de Lange, & Jensen, 2014;De Graaf et al, 2013;Chakravarthi & VanRullen, 2012;Romei, Gross, & Thut, 2012;Dugué, Marque, & VanRullen, 2011;Haegens, Nácher, Luna, Romo, & Jensen, 2011;Busch, Dubois, & VanRullen, 2009). Also, given that the period of this oscillation is of 100 msec, it might be the neural basis of discrete perception (VanRullen & Koch, 2003;Harter, 1967).…”
Section: Introductionmentioning
confidence: 99%
“…This indicates entrainment is an adaptable mechanism that can operate for naturalistic, not precisely rhythmic, stimuli (Box 2). Alpha oscillations entrained by rhythmic pulses of transcranial brain stimulation altered detection of auditory [27] and visual [28] stimuli depending on entrained oscillatory phase.…”
Section: Entrainment Of Intrinsic Neural Oscillationsmentioning
confidence: 99%
“…Specifically for alpha-frequency, and in a retinotopically specific location, visual performance was enhanced, directly demonstrating the causal relevance of these oscillatory patterns for conscious vision. Rhythmic TMS was recently used to confirm also the functional relevance of alpha phase for visual perception (Jaegle and Ro, 2014). Helfrich et al (2014) recently demonstrated, using simultaneous EEG and tACS, that alpha oscillations can successfully be induced by tACS at the same frequency, moreover with perceptual consequences.…”
Section: Advanced Nibs Protocols and The Study Of Conscious Visionmentioning
confidence: 99%